PENINGKATAN KEMAMPUAN SISWA KELAS VIII SMP NEGERI 14 SIGI MENULIS CERPEN MELALUI METODE LATIHAN - Nasim Taha (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2022)
The main problem in this research is the low student learning outcomes in short story writing material. Therefore, to improve students' abilities and maximize learning, the researchers used the Exercise method. The research subjects were all 20 students, namely 9 boys and 11 girls. The method used in this research is the exercise method. The design of this study refers to the Kemmis and Mc Taggart model which consists of four components, namely 1) planning, 2) action implementation, 3) observation and 4) reflection. The data collected in this study is in the form of teacher and student activity data during the learning process obtained by using observation sheets and student learning outcomes data obtained by giving individual tests to students. In the research that has been carried out, the results showed that students experienced an increase of 90%. The increase in classical absorption in cycle II was caused because the researchers put more emphasis on mastering concepts in writing short stories using the Exercise method. While in the first cycle, the researcher did not emphasize the mastery of the concept. Based on these results, it can be concluded that the application of the Exercise method can improve student learning outcomes and deserves to be considered as material for classroom action research for teachers